Reversion of AHRR Demethylation Is a Quantitative Biomarker of Smoking Cessation - Philibert, Robert; Hollenbeck, Nancy; Andersen, Eleanor; McElroy, Shyheme; Wilson, Scott; Vercande, Kyra; Beach, Steven R. H.; Osborn, Terry; Gerrard, Meg; Gibbons, Frederick X.; Wang, Kai (Frontiers in Psychiatry, 2016)
Smoking is the largest preventable cause of morbidity and mortality in the world. Although there are effective pharmacologic and behavioral treatments for smoking cessation, our inability to objectively quantify smokers’ progress in decreasing smoking has been a barrier to both clinical and research efforts. In prior work, we and others have shown that DNA methylation at cg05575921, a CpG residue in the aryl hydrocarbon receptor repressor (AHRR), can be used to determine smoking status and infer cigarette consumption history. In this study, we serially assessed self-report and existing objective markers of cigarette consumption in 35 subjects undergoing smoking cessation therapy, then quantified DNA methylation at cg05575921 at study entry and three subsequent time points. Five subjects who reported serum cotinine and exhaled carbon monoxide verified smoking abstinence for the three months prior to study exit averaged a 5.9% increase in DNA methylation at cg05575921 (p<0.004) over the six month study. Although the other 30 subjects did not achieve smoking cessation at the six-month time point, their self-reported reduction of cigarette consumption (mean = 6 cigarettes per day) was associated with a 2.8% increase DNA methylation at cg05575921 (p<0.05). Finally, a survey of subjects as they exited the study demonstrated strong support for the clinical use of epigenetic biomarkers. We conclude that AHRR methylation status is a quantifiable biomarker for progress in smoking cessation that could have substantial impact on both smoking cessation treatment and research.